Sistem Perbandingan Data Kependudukan di Indonesia dan Malaysia - Siagian, Zevanya Angelica Putri; Dompak, Timbul (Prosiding, 2024)
By 2024, both countries have developed a sophisticated system to track their citizens' data. Indonesia uses cloud-based systems and AI to analyze population data. Meanwhile, Malaysia relies on 5G and LoT networksto collect citizens' data in real time. In this article we will discuss the population data system of Indonesia and Malaysia in 2024. We will also explore the challenges and opportunities of using this new technology. This research uses qualitative research methods. Research data is collected from interviews, observations, and documentation. Subjects of comparison are further defined as procedures for registration of population, identification, data management, and models of immigration-related policies